1996
DOI: 10.1139/m96-143
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Pseudomonas aureofaciens from the rhizosphere to aerial plant tissue

Abstract: Following inoculation onto seeds, the rhizobacterium Pseudomonas aureofaciens Ps3732RNL11 (L11), which contains the constituitively expressed lacZ and lacY genes from Escherichia coli, was recovered from the interior of aerial tissues of all 16 monocot and dicot plants tested, and the exterior of aerial surfaces of 15. In more detailed studies with corn, wheat, and broccoli, both Ps3732RNL11 and its nonengineered parent strain PS3732RN (RN) rapidly established large populations on all root systems and smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 21 publications
2
58
0
5
Order By: Relevance
“…luteus were also isolated, albeit at low frequencies, from the roots of rice plants cultivated in a paddy field (23). Since various bacterial species can invade from the rhizosphere to the root through wounds formed concomitant with lateral root emergence and root tip elongation (2,8,14,15,18,21,32,34,46), endophytic bacteria that originate from rice seeds may become a minor population in the bacterial community in the roots of the mature rice plants. A great variety of bacteria live in the rhizosphere, and interact with plants.…”
Section: Resultsmentioning
confidence: 99%
“…luteus were also isolated, albeit at low frequencies, from the roots of rice plants cultivated in a paddy field (23). Since various bacterial species can invade from the rhizosphere to the root through wounds formed concomitant with lateral root emergence and root tip elongation (2,8,14,15,18,21,32,34,46), endophytic bacteria that originate from rice seeds may become a minor population in the bacterial community in the roots of the mature rice plants. A great variety of bacteria live in the rhizosphere, and interact with plants.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effect and role of IAA production by endophytic bacteria in growth promotion of sugarcane need to be investigated, this trait was considered one of the major mechanisms involved in maize growth promotion by the rhizosphere bacteria Gluconacetobacter azotocaptans DS1, Pseudomonas putida CQ179, and Azospirillum lipoferum N7 under greenhouse conditions (60). Several studies have reported that endophytic microbial communities originate from the soil and rhizosphere (25,47). The observation that the frequency of IAA-producing bacteria is higher in the stems than in the rhizosphere of sugarcane plants suggests that the plant selects for endophytic bacteria with this trait or that IAA-producing bacteria harbor other traits that allow them to more effectively reach and establish themselves in the inner plant tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Following colonization of the root interior, PsJN colonizes stems and leaves. Other studies have also detected endophytes within aerial plant parts, including stems, leaves, and flowers (28,34,46,52). It has been suggested that bacteria can be transported in xylem vessels through the transpiration stream (16, 19, 22, 23, 54) or by colonizing intercellular spaces from roots to aerial parts (10,16).…”
Section: Discussionmentioning
confidence: 99%